ANALISIS KONFLIK DALAM NOVEL SITI RAYATI KARYA MOH. SANOESI (KAJIAN PSIKOLOGI SASTRA) - Revi Sundari Utami; Fajar Sukma Nur Alam (Universitas Batanghari, 2025)
This study focuses on the analysis of character conflicts in the novel Siti Rayati by Moh. Sanoesi using a study of literary psychology. The purpose of this study is to describe the form of conflict in the novel Siti Rayati by Moh. Sanoesi. This research is a literature study. The method used in this study is a descriptive analysis method using a qualitative approach. The data source in this study is the novel Siti Rayati by Moh. Sanoesi published by PT Kiblat Buku Utama, second edition in 2020. The data collection technique used is the reading and note-taking technique. The results of this study indicate that the conflicts in the novel Siti Rayati by Moh. Sanoesi, namely internal conflict and external conflict. The internal conflict consists of feelings of longing, feelings of fear, feelings of restlessness, feelings of confusion, feelings of sadness and feelings of worry. Meanwhile, external conflicts consist of social conflicts between Patimah and Tuan Steenhart, social conflicts between Siti Rayati and Juragan Wadana, social conflicts between Siti Rayati and Dalem Istri, social conflicts between Tuan Steenhart and Mandor Sastra, social conflicts between Tuan Steenhart and Tukang Kebon and social conflicts between Tuan Steenhart and Mandor